A brief assessment of Singapore's economic miracle - Khan, Habibullah (The Philippine Review of Business and Economics, 1996)
After reviewing Singapore's economic performance in the past three decades, the paper seeks to identify the reasons for Singapore's success by adopting a political economy approach. It is argued that Singapore adopted a balanced combination of market and government and its economic philosophy closely reflected the governed market theory based on developmental state model. Although government intervention in Singapore was fairly extensive, the interventionist measures did not distort market efficiency due to the high quality of political leadership, pragmatism, meritocracy and social conformism. The future outlook for Singapore economy remains bright and such an optimism is based on improvements in its educational standards, training programs, and stringent criteria of recruitment in the administrative service, as argued in the paper.